Visible light induced photocatalytic inactivation of bacteria by modified titanium dioxide films on organic polymers. Issue 3 (25th September 2014) - Sadowski, Rafał; Strus, Magdalena; Buchalska, Marta; Heczko, Piotr B.; Macyk, Wojciech
Abstract : A transparent polypropylene foil pre-treated with a low temperature plasma and covered with sensitized, nanocrystalline TiO2 thin film, appears to be a useful, self-sterilizing material activated upon visible light irradiation. Abstract : Commercially available polypropylene foil was pretreated with a low temperature oxygen plasma and covered with a thin film of nanocrystalline titanium dioxide by dip coating. The films were then photosensitized by titanium(iv ) surface charge transfer complexes formed by impregnation with catechol. The photoactivity of the coatings up to 460 nm was confirmed by photoelectrochemical measurements. The photoinactivation of Escherichia coli and Staphylococcus aureus was evaluated by a glass adhesion test based on ISO 27447:2009(E) in the presence of visible light. The coating showed good antimicrobial activity induced by light from a light-emitting diode (405 nm), in particular towards E. coli ATCC 25922 strain. Adaptation of ISO 27447:2009(E) to assess bacterial photoinactivation by photocatalytic coatings will allow this procedure to be applied for the comparison of photoactivity under a range of irradiation conditions.